Effect of aluminium on the microstructure and mechanical properties of as-cast magnesium–manganese alloys. Issue 17 (22nd November 2017) - Yu, Zhengwen; Hu, Mengdie; Tang, Aitao; Wu, Mingsong; He, Jiejun; Gao, Zhengyuan; Wang, Fangyuan; Li, Caiyu; Chen, Bin; Liu, Jianguo
ABSTRACT: In this paper, the effect of aluminium on microstructure and mechanical properties of as-cast magnesium–manganese alloy has been investigated by means of X-ray diffraction, optical microscopy and scanning electron microscopy. The results reveal that various Al–Mn intermetallic compounds form with an increase of Al content. As a result, microstructure of AM11 alloy has been effectively refined due to the formation of Al8 Mn5 phase along the grain boundary, while Al addition is explained as the main reason on refining the microstructure of AM91 alloy due to its higher grain growth restriction factor value of ∼4.32. The tensile yield strength (TYS) has been improved steadily from 27.4 to 122.9 MPa with increasing Al content, because of the combined effects of grain boundary strengthening, solid solution strengthening and precipitation hardening behaviours.